A miracle in a dairy shop: On a typology of an “emigrant” novel - Tatiana Marchenko (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2020)
Alja Rachmanowa (real name Galina Dyuryagina-Hoyer) is a Russian writer with a European success in 1930s. Her books were published in German translation made by her husband Arnulf Hoyer, and still remain obscure in Russia. The phenomenon is rather fascinating from the point of view of typology of émigré prose. A novel “Milchfrau in Ottakring” (1933) of the prolific author of three dozen books was extremely popular, not only it remains relevant, but looks very modern as an “emigrant” novel of special type. In a diary form based on a personal experience, the writer sets out a story of success. A qualified philologist, Alja Rachmanowa (her literary pseudonym is usually referred to) was forced to become for a couple of years a saleswoman in a rented dairy shop. This experience of a “foreigner”, her national and sociocultural identity, adaptation, and ultimately successful integration are reflected in the diary autobiographical novel. The Russian component of the book in German whose author / heroine balances between the spheres of “own” and “stranger,” has driven a success of the “Milchfrau in Ottakring”. Russian realities, Russian mentality, nostalgie for the native country permeating the narration, especially attracted the readership. One of the important markers of “Russianness” is a citation of Russian literature, not in the form of a mere quotation, but as a rethinking, re-interpretation, a dispute with the classics. The article deals with some examples of such citing (F.M. Dostoevsky, A.V. Koltsov, A.N. Pleshcheev, Z.N. Gippius). A fragment of the novel in Russian translation is given in Annex.